High Wall Shear Stress can Predict Wall Degradation in Ascending Aortic Aneurysms: An Integrated Biomechanics Study - Salmasi, M. Yousuf; Pirola, Selene; Sasidharan, Sumesh; Fisichella, Serena M.; Redaelli, Alberto; Jarral, Omar A.; O’Regan, Declan P.; Oo, Aung Ye; Moore, James E.; Xu, Xiao Yun; Athanasiou, Thanos (Frontiers in Bioengineering and Biotechnology, 2021)
Background. Blood flow patterns can alter material properties of ascending thoracic aortic aneurysms (ATAA) via vascular wall remodeling. This study examines the relationship between wall shear stress (WSS) obtained from image-based computational modelling with tissue-derived mechanical and microstructural properties of the ATAA wall using segmental analysis. Methods. Ten patients undergoing surgery for ATAA were recruited. Exclusions: bicuspid aortopathy, connective tissue disease. All patients had pre-operative 4-dimensional flow magnetic resonance imaging (4D-MRI), allowing for patient-specific computational fluid dynamics (CFD) analysis and anatomically precise WSS mapping of ATAA regions (6 -12 segments per patient). ATAA samples were obtained from surgery and subjected to region-specific tensile and peel testing (matched to WSS segments). Computational pathology was used to characterize elastin/collagen abundance and smooth muscle cell (SMC) count. Results. Elevated values of WSS were predictive of: reduced wall thickness (coef -0.0489, 95% CI [-0.0905, -0.00727], p=0.022) and dissection energy function (longitudinal) (-15,0, 95% CI [-33.00, -2.98], p=0.048). High WSS values also predicted higher ultimate tensile strength (coef 0.136, 95% CI, [0 .001, 0.270], p=0.048). Additionally, elevated WSS also predicted a reduction in elastin levels (coef -0.276, 95% [CI -0.531, -0.020], p=0.035) and lower SMC count (coef -6.19, 95% CI [-11.41, -0.98], p=0.021). WSS was found to have no effect on collagen abundance or circumferential mechanical properties. Conclusions. Our study suggests an association between elevated WSS values and aortic wall degradation in ATAA disease. Further studies might help identify threshold values to predict acute aortic events.